Posterior Cranial Vault Distraction Osteogenesis Utilizing a Posterior—Superior Distraction Vector in the Treatment of Mercedes Benz Pattern Craniosynostosis. Issue 6 (September 2021) - Marji, Fady P.; Block, Lisa M.; Anstadt, Erin E.; Dvoracek, Lucas A.; Bruce, Madeleine K.; Williams, Abraham A.; Hall, Jennifer A.; Losee, Joseph E.; Goldstein, Jesse A.
Abstract : Abstract: Bilateral lambdoid and sagittal synostosis, or Mercedes Benz Syndrome, is a rare complex craniosynostosis resulting in frontal bossing, a tapered posterior fossa, and an anteriorly displaced cranial vertex. Its ideal surgical correction must result in posterior expansion, skull elongation, and caudal repositioning of the vertex. We present a craniometric analysis of skull changes with posterior-superior distraction and introduce a novel craniometric measure: vertex position. In this study, a retrospective review was performed to analyze outcomes of posterior cranial vault distraction osteogenesis (PVDO) using a posterior–superior distraction vector from 2016 to 2019. Cranial vertex position was measured as a fraction of the occipitofrontal diameter from rostral to caudal (0–1.0). Four patients underwent PVDO at mean age 10.61 ± 3.16 months utilizing a posterior–superior distraction vector. Linear distraction distance averaged 30.30 ± 0.90 mm with a mean consolidation period of 3.98 ± 0.72 months. Mean corrected change in intra-cranial volume was 236.30 ± 3.71 mL, at an average rate of 7.81 ± 2.00 mL/mm of distraction. Increases in anterior cranial height (7.83 ± 2.51 mm), middle cranial height (8.43 ± 4.21 mm), posterior cranial height (13.15 ± 7.45 mm), and posterior cranial fossa height (21.99 ± 8.55 mm) were observed. Cranial vertex demonstrated a mean posterior movement of 0.18 ± 0.13. PVDO utilizing a posterior-superior distraction vector for management of nonsyndromic bilateral lambdoid and sagittal synostosis effectively increases intracranial volume and height and provides an esthetic outcome with posterior movement of the cranial vertex. Abstract : Supplemental Digital Content is available in the text